A double-end-beam based infrared device fabricated using CMOS-MEMS process. Issue 3 (20th June 2016) - Lei, Cheng; Mao, Haiyang; Yang, Yudong; Ou, Wen; Xue, Chenyang; Yao, Zong; Ming, Anjie; Wang, Weibing; Wang, Ling; Hu, Jiandong; Xiong, Jijun
Abstract : Purpose: Thermopile IR detectors are one type of the most important IR devices. Considering that the surface area of conventional four-end-beam based thermopile devices cannot be effectively utilized and the performance of this type of devices is relatively low, so the paper presents a double-end-beam based thermopile device with high duty cycle and performance. The paper aims to discuss these issues. Design/methodology/approach: Numerical analysis was conducted to show the advantages of the double-end-beam based thermopile devices. Findings: Structural size of the double-end-beam based thermopiles may be further scaled down and maintain relatively higher responsivity and detectivity when compared with the four-end-beam based thermopiles. We characterized the thermoelectric properties of the device proposed in this paper, which achieves a responsivity of 1151.14 V/W, a detectivity of 4.15×108 cm Hz1/2/W, and a response time of 14.46 ms. Originality/value: The paper proposed a micro electro mechanical systems (MEMS) thermopile infrared sensor based on double-end-beam structure.